A Development of Low Cost Wi-Fi Robot for Teaching Aid - Nur Uddin (JURNAL INFOTEL, 2020)
A low-cost Wi-Fi robot as a teaching equipment is developed. The robot can be used to teach students in the subjects related to robotics system and internet of things (IoT). A Wi-Fi robot is a robot equipped with a Wi-Fi communication system for connecting to the internet. Integrating the robot with an IoT platform makes the robot able to communicate with other devices. The developed Wi-Fi robot in this study is a three-wheeled robot type. A NodeMCU ESP-12, which is a microcontroller equipped with Wi-Fi module, is applied in the robot. The robot is connected to the Blynk IoT platform and paired to a smartphone. It results in communication between the robot and the smartphone through the internet. The communication is demonstrated by remotely operating the robot using the smartphone. Mechanical structure and electronic wiring of the robot are simple such that the robot is easily built. Moreover, the cost of required components for building the robot is quite cheap as less than USD 20.